Molecular identification and antibiogram profiles of respiratory bacterial agents isolated from cattle reared in some selected areas of Mymensingh division, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Respiratory bacterial infections in cattle are very common all over Bangladesh causing high economic loss. This research was performed with a view to proper control of respiratory bacterial infections of cattle in Bangladesh. A total of 100 nasal samples were collected on the basis of clinical signs. From the collected samples isolation, identification and characterization of the bacterial agents was done using cultural, biochemical and molecular techniques. Antibiogram profiles of the isolated agents were studied by disc diffusion method. Pasteurella multocida, Staphylococcus aureus and Escherichia coli were successfully isolated and identified from the collected samples. The isolated Pasteurella multocida produced small, round, opaque colonies on blood agar; Staphylococcus aureus produced golden yellow colony in mannitol salt agar; E. coli produced black color colonies with metallic sheen on EMB agar. Pasteurella multocida showed Gram negative, bipolar rods. Staphylococcus aureus showed Gram positive, cocci shaped and E. coli showed Gram negative, small rod shaped. Among 100 nasal samples 16 were found to be positive for Pasteurella multocida, 21 for Staphylococcus aureus and 13 for E. coli on the basis of cultural and biochemical characteristics. The antibiogram study reflected that ciprofloxacin, tetracycline and chloramphenicol should be first choice of treatment of respiratory bacterial infections caused by the isolated 3 bacteria. Pasteurella multocida was further characterized by PCR where 16 isolates showed positive band at 460 bp and Pasteurella multocida type A at 1044 bp. The present research work covering antibiogram study is a preliminary report in the context of Bangladesh.Asian Australas. J. Biosci. Biotechnol. 2019, 4 (1), 60-66